2017
DOI: 10.3892/ol.2017.5662
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the efficacy of amrubicin and the previous chemotherapy regimen for relapsed small cell lung cancer

Abstract: Abstract. Amrubicin has been demonstrated to be beneficial in the treatment of patients with relapsed small cell lung cancer (SCLC). The aim of the present study was to evaluate whether there is a significant difference in the efficacy of amrubicin between patients with relapsed SCLC who were previously treated with a platinum agent in combination with a topoisomerase I inhibitor, and those patients previously treated with a platinum agent in combination with a topoisomerase II inhibitor. The medical records o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A result of a phase II study evaluating the efficacy of amrubicin monotherapy for relapsed SCLC suggested that the absence of any significant difference in the PFS by amrubicin therapy was dependent on the previous platinum-and topoisomerase inhibitor-based therapies [18]. In addition, we previously reported that no significant difference was observed in the efficacy of amrubicin monotherapy according to the type of prior regimen, such as cisplatin plus irinotecan (a topoisomerase I inhibitor), or a platinum agent plus etoposide [19]. Accordingly, it may be worth noting that carboplatin plus etoposide can be expected to show effectiveness, regardless of the type of prior regimen, including amrubicin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A result of a phase II study evaluating the efficacy of amrubicin monotherapy for relapsed SCLC suggested that the absence of any significant difference in the PFS by amrubicin therapy was dependent on the previous platinum-and topoisomerase inhibitor-based therapies [18]. In addition, we previously reported that no significant difference was observed in the efficacy of amrubicin monotherapy according to the type of prior regimen, such as cisplatin plus irinotecan (a topoisomerase I inhibitor), or a platinum agent plus etoposide [19]. Accordingly, it may be worth noting that carboplatin plus etoposide can be expected to show effectiveness, regardless of the type of prior regimen, including amrubicin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we previously reported that no significant difference was observed in the efficacy of amrubicin monotherapy according to the type of prior regimen, such as cisplatin plus irinotecan (a topoisomerase I inhibitor), or a platinum agent plus etoposide [19]. Accordingly, it may be worth noting that carboplatin plus etoposide can be expected to show effectiveness, regardless of the type of prior regimen, including amrubicin.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the influence of pretreatment with etoposide on the efficacy of AMR has not been established. Although it has been reported to be an influencing factor, 1 conflicting data that pretreatment with etoposide is not related to efficacy have also been reported 8 . Thus, the clinical characteristics of the optimal patient population for AMR treatment remain unclear.…”
Section: Introductionmentioning
confidence: 99%